2015
DOI: 10.1063/1.4907555
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of a concave nosed axisymmetric body on a free surface

Abstract: We report on an experimental study of the vertical impact of a concave nosed axisymmetric body on a free surface. Previous studies have shown that bodies with a convex nose, like a sphere, produce a well defined splash with a relatively large cavity behind the model. In contrast, we find that with a concave nose, there is hardly a splash and the cavity extent is greatly reduced. This may be explained by the fact that in the concave nosed case, the initial impact is between a confined air pocket and the free su… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 15 publications
3
9
1
Order By: Relevance
“…The role of confined air in reducing the peak pressure was also described by Mathai et al. (2015), who found that a concave-nosed body exhibited a smaller peak pressure than a flat or convex-nosed body because of the presence of trapped air. In summary, our systematic experimentation has revealed that the compression and depressurization of trapped air bubbles during the initial impact phase leads to the rise and fall of the impact force and accounts for a reduction in the peak impact force.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…The role of confined air in reducing the peak pressure was also described by Mathai et al. (2015), who found that a concave-nosed body exhibited a smaller peak pressure than a flat or convex-nosed body because of the presence of trapped air. In summary, our systematic experimentation has revealed that the compression and depressurization of trapped air bubbles during the initial impact phase leads to the rise and fall of the impact force and accounts for a reduction in the peak impact force.…”
Section: Resultssupporting
confidence: 53%
“…Regarding axisymmetric slender bodies with different nose geometries pointing downward, those with ogive noses experience much smaller impact forces than those with flat noses (Bodily, Carlson & Truscott 2014). Mathai, Govardhan & Arakeri (2015) reported a reduction in peak pressure with a concave-nosed body, the result of air trapped inside the concave hole. In addition to a change in object shape, the conditions surrounding an impacting object were varied.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally, these oscillations have a different origin from slamming itself. Flat (and concave) surfaces trap air bubbles in the process of piercing the water surface, and the oscillations of these bubbles have been found to give rise to the fluctuations in the force measurements ( 27 ). Assuming that the concave arch supporting human feet traps a bubble of radius w 2 (width of the feet model as shown in fig.…”
Section: Resultsmentioning
confidence: 99%
“…By optimizing their toe’s shapes and striking posture, basilisk lizards can stabilize the air cavity long enough to supply sufficient upward support. Therefore, the geometric shape of the solid objects plays an equally important role in creating, regulating, and stabilizing the underwater air–water interface; however, it is often ignored. In fact, the geometric shape [i.e., axisymmetric slender bodies (always cylinders) and spheres] and nose shape of objects (i.e., cone, ogive, flat, hemisphere, and concave) significantly influence the water entry, cavity formation, and cavity stabilization processes.…”
Section: Introductionmentioning
confidence: 99%